Transcriptomic Analyses Shed Light on Critical Genes Associated with Bibenzyl Biosynthesis in Dendrobium officinale - Adejobi, Oluwaniyi Isaiah (Plants (Basel), 2021)
The Dendrobium plants (members of the Orchidaceae family) are used as traditional Chinese medicinal herbs. Bibenzyl, one of the active compounds in Dendrobium officinale, occurs in low amounts among different tissues. However, market demands require a higher content of thes compounds to meet the threshold for drug production. There is, therefore, an immediate need to dissect the physiological and molecular mechanisms underlying how bibenzyl compounds are biosynthesized in D. officinale tissues. In this study, the accumulation of erianin and gigantol in tissues were studied as representative compounds of bibenzyl. Exogenous application of Methyl-Jasmonate (MeJA) promotes the biosynthesis of bibenzyl compounds; therefore, transcriptomic analyses were conducted between D. officinale-treated root tissues and a control. Our results show that the root tissues contained the highest content of bibenzyl (erianin and gigantol). We identified 1342 differentially expressed genes (DEGs) with 912 up-regulated and 430 down-regulated genes in our transcriptome dataset. Most of the identified DEGs are functionally involved in the JA signaling pathway and the biosynthesis of secondary metabolites. We also identified two candidate cytochrome P450 genes and nine other enzymatic genes functionally involved in bibenzyl biosynthesis. Our study provides insights on the identification of critical genes associated with bibenzyl biosynthesis and accumulation in Dendrobium plants, paving the way for future research on dissecting the physiological and molecular mechanisms of bibenzyl synthesis in plants as well as guide genetic engineering for the improvement of Dendrobium varieties through increasing bibenzyl content for drug production and industrialization.